Dragkamp og balansegang. Frigjøringsmarkeringene i Kirkenes 1954–1994: Et minnepolitisk perspektiv - Kari Aga Myklebost; Joakim Aalmen Markussen (Nordisk Østforum, 2021)
Abstract: Commemorating the Red Army Liberation in Kirkenes, Norway, 1954–1994 Abstract: Commemorating the Red Army Liberation in Kirkenes, Norway, 1954–1994 This study traces the development over fifty years of the joint Norwegian–Soviet/Russian commemorations of the Red Army liberation of the eastern part of Finnmark County, Norway, in October 1944. The first commemorative events were held in October 1954 in the town of Kirkenes close to the Norwegian–Soviet border. Throughout the Cold War and into the post-Soviet period, such events have been arranged in Kirkenes every five years, with representatives of the Norwegian state authorities acting as hosts to a Soviet/Russian delegation. The focal point of these events has been a ceremony held by the Liberation Monument, unveiled in 1952 to honour the Red Army soldiers who liberated Norwegian territory by driving back the Nazi occupation forces. This article documents how the tradition of joint commemorations developed across the Iron Curtain divide as part of a predominantly diplomatic struggle over the events of October 1944, between Norway, a small state and NATO-member, and the superpower that was the Soviet Union. Our study concludes that, despite the struggle, which stemmed from Cold War tensions and competing security perceptions and interests, these joint commemorations have served as a stabilizing element in bilateral relations, producing a narrative not only about the Red Army liberation of eastern Finnmark, but also of friendship and mutual respect between the peoples of Norway and Russia, and of a long tradition of peaceful relations between the two states.